Penyuluhan Tentang Bahaya Pestisida Pada Petani - Kafit, M; Rasuanto, Budi; Febryanti, Darna (ASOSIASI IDEBAHASA KEPRI, 2024)
Pesticides are the synthesis of a mixture of chemicals that function to eradicate pest organisms (pests/weeds), reduce pest populations, and control disease, so that widespread attacks can be prevented. However, in practice pesticides cause side effects that are detrimental to humans and the surrounding environment. For humans, pesticides can cause irritation to the membranes of the eyes and skin, and various other impacts. Pesticides contain dangerous chemicals, so appropriate procedures are required to ensure they are not dangerous to use. This service method uses an extension method preceded by filling out a questionnaire as a tool to measure farmers' level of knowledge before providing extension. The activity continued with education about the dangers of pesticides and an introduction to the use of complete personal protective equipment (PPE). The results of the initial questionnaire filling show that farmers' knowledge of the dangers of pesticides is still low, and the use of PPE when working with pesticides is incomplete. These results are then followed up with the implementation of counseling. After the counseling was carried out, it was followed by a discussion session with farmers about knowledge and good use of PPE. Based on the results of this service activity, it can be concluded that one way to increase farmers' knowledge is by conducting outreach. With this increase in knowledge, it is hoped that the incidence of health problems due to pesticide exposure for farmers in the future can be reduced significantly.